2017
DOI: 10.2135/cropsci2016.10.0880
|View full text |Cite
|
Sign up to set email alerts
|

Drought Response and Genetic Diversity in Pisum fulvum, a Wild Relative of Domesticated Pea

Abstract: Productivity of grain crops in semi‐arid environments is often affected by drought, which is likely to increase due to predicted climate changes. Wild pea (Pisum fulvum Sibth. & Smith, Pf) accessions sampled across its ecological amplitude in Israel (350–850 mm annual precipitation) were used to assess the genetic diversity for drought responses. We hypothesized that native species evolving under Eastern Mediterranean climate carry adaptive traits to cope with drought stress. Accessions were classified accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…Potential drought tolerance traits in CWR include leaf waxiness found in P. sativum , root architecture, and Rhizobial associations. P. fulvum also exhibits lower drought susceptibility and could potentially be a source for drought tolerance (Naim‐Feil et al, 2017). There are uninvestigated possibilities to explore wild peas from extreme environments in Central Asia and arid Middle East for abiotic stress tolerances based on environmental parameters and prioritization of accessions for controlled environment studies.…”
Section: Peamentioning
confidence: 99%
“…Potential drought tolerance traits in CWR include leaf waxiness found in P. sativum , root architecture, and Rhizobial associations. P. fulvum also exhibits lower drought susceptibility and could potentially be a source for drought tolerance (Naim‐Feil et al, 2017). There are uninvestigated possibilities to explore wild peas from extreme environments in Central Asia and arid Middle East for abiotic stress tolerances based on environmental parameters and prioritization of accessions for controlled environment studies.…”
Section: Peamentioning
confidence: 99%
“…This matches the results of Naim-Feil et al (2017), although our genetic clusters do not fully correspond to theirs. Naim-Feil et al (2017) suggested that a recent range expansion or seed transfer by migrating herbivores might explain the observed genetic structure. However, we did not detect an increase of the effective population size in the recent past.…”
Section: Discussionmentioning
confidence: 99%
“…Nine accessions of P. fulvum , representing a wide sample of the genetic diversity in this species, were generously provided by Dr. S. Abbo, The Hebrew University, Rehovot, Israel. Passport data for these can be obtained in Naim-Feil et al (2017) . Two additional samples of P. fulvum from Israel (VIR 6070 and VIR 6071) were kindly supplied by Dr. F. Gorel, then at the Institute of Cytology & Genetics, Novosibirsk, Russia.…”
Section: Methodsmentioning
confidence: 99%